2016
DOI: 10.1002/lt.24650
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of temporary portocaval shunt during orthotopic liver transplantation with vena cava preservation: A propensity score analysis

Abstract: During orthotopic liver transplantation (OLT), clamping of the portal vein induces splanchnic venous congestion and accumulation of noxious compounds. These adverse effects could increase ischemia/reperfusion injury and subsequently the risk of graft dysfunction, especially for grafts harvested from extended criteria donors (ECDs). Temporary portocaval shunt (TPCS) could prevent these complications. Between 2002 and 2013, all OLTs performed in our center were retrospectively analyzed and a propensity score mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
18

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 26 publications
0
30
0
18
Order By: Relevance
“…However, multivariate analysis showed only laboratory MELD and IAR to be individual determinants of perioperative transfusion of RBCs, whereas the interaction between IAR and TPCS was low ( P = 0.54). The beneficial effect of a TPCS, by using univariate analysis, has been described before (Table ) . These studies do not describe the order of reperfusion used during transplantation, although we assume that portal reperfusion was first.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, multivariate analysis showed only laboratory MELD and IAR to be individual determinants of perioperative transfusion of RBCs, whereas the interaction between IAR and TPCS was low ( P = 0.54). The beneficial effect of a TPCS, by using univariate analysis, has been described before (Table ) . These studies do not describe the order of reperfusion used during transplantation, although we assume that portal reperfusion was first.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effect of a TPCS, by using univariate analysis, has been described before (Table 8). (7,(26)(27)(28) These studies do not describe the order of reperfusion used during transplantation, although we assume that portal reperfusion was first. A meta-analysis performed by Pratschke et al showed a significant beneficial effect of a TPCS on operative blood loss, but the I 2 values indicated substantial heterogeneity among the studies (P < 0.05), which could bring a potential bias to the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver transplantation (LT), whether deceased donor (DDLT) or living donor (LDLT), is the most appropriate approach in adult and pediatric patients to treat end-stage liver disease and it is an effective therapeutic modality to increase patient survival time [ 1 ]. Nowadays, we observe an important improvement in medical (drugs) to prevent or treat transplant rejections and infections, better intensive care, and improved anesthetic, hemodynamic, and surgical approaches [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…A temporary bypass, the temporary portocaval shunt (TPCS), can be used and is associated with the use of the piggyback technique during hepatectomy to reduce pressure in the portal system and facilitate dissection of the retrohepatic vena cava [ 1 ]. The TPCS can have different anastomosis: end-to-side or passive portocaval tubing shunt.…”
Section: Introductionmentioning
confidence: 99%